Cost‐effective strategies to increase the capture of target species for trap networks in Aotearoa New Zealand - Mairi Hilton; Christine Stockum; Paul Ward; Jamie McNaught; Jim Roberts (Conservation Science and Practice)
Abstract The Capital Kiwi Project recently led an initiative to reintroduce North Island Brown Kiwi (Apteryx mantelli) to the southwestern hills of Wellington City in Aotearoa New Zealand (NZ), where they had been absent in the wild for over a century, largely due to predation by introduced stoats (Mustela erminea). The kiwi were released after a substantial effort to reduce stoat populations using an extensive network of ground traps, but stoats remained present in the area. Efforts to target stoats were hampered by catching significant numbers of non‐target species (particularly hedgehogs, Erinaceus europaeus), precluding the ability to catch stoats until the traps were manually reset. We therefore conducted two trials to assess the ability to reduce the capture of hedgehogs, freeing the traps to be available to catch stoats. The first trial involved raising a portion of traps 10 cm off the ground and comparing the catch composition of raised vs. unraised traps. The second involved using two different types of trap and comparing the catch composition between the two types. We found that raised traps and the smaller trap type both significantly improved species catch composition compared to unraised and larger trap type, catching fewer hedgehogs and more stoats, although results varied by month and across the project area. Our project provides the first large‐scale study of simple, cost‐effective methods to decrease the capture of non‐target species in a trap network targeting stoats in Aotearoa NZ. Our results are relevant to other trapping programs aiming to reduce the capture of non‐target species to more effectively target stoats, with the hope of improving conservation outcomes for native wildlife.